Maternal Decisions on Prelacteal Feeding Practices for Newborns using the Theory of Planned Behavior Approach in Grogol, Sukoharjo, Central Java, Indonesia - Arjuna Pratama Waruwu; Haryani Saptaningtyas; Revi Gama Hatta Novika; Eti Poncorini Pamungkasari Pamungkasari; Ika Sumiyarsi Sukamto (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Exclusive breastfeeding is essential for optimal infant health, yet its coverage in Indonesia remains suboptimal, partly due to prelacteal feeding practices that interfere with breastfeeding initiation and increase health risks for newborns. The purpose of this study was to examine how maternal intention and prelacteal feeding habits are impacted by attitude, subjective standards, and perceived behavioral control among postpartum mothers. Subjects and Method: This was a quantitative observational study employing a cross-sectional design, conducted in Grogol District, Sukoharjo, Central Java, Indonesia, from February to March 2026. A total of 82 postpartum mothers ≤42 days after delivery were chosen using total sampling. The independent factors were attitude, subjective norms, perceived behavioral control, and intention, and the dependent variable was prelacteal feeding practice. A structured questionnaire was used to collect the data, and logistic regression was used for analysis. Results: Subjective norms (OR= 3.12; 95% CI= 1.15 to 8.64; p= 0.012) and perceived behavioral control (OR= 5.16; 95% CI= 1.83 to 14.79; p<0.001) were significantly associated with maternal intention. Intention (OR= 2.68; 95% CI= 0.99 to 7.27; p= 0.029) and perceived behavioral control (OR= 4.69; 95% CI= 1.67 to 13.45; p<0.001) were significantly associated with prelacteal feeding practices. In multivariate analysis, perceived behavioral control remained the strongest determinant of intention (OR= 6.88;95% CI= 1.63 to 28.92; p= 0.008) and prelacteal feeding practice (OR= 4.26; 95 % CI= 1.62 to 11.17; p= 0.003). Conclusion: The most significant factor influencing mother intention and prelacteal feeding practices was perceived behavioral control. Health promotion strategies should focus on reducing breastfeeding barriers and strengthening family and healthcare support.